Fixed-dose combination bictegravir, emtricitabine, and tenofovir alafenamide in adolescents and children with HIV: week 48 results of a single-arm, open-label, multicentre, phase 2/3 trial - Gaur, Aditya H.; Cotton, Mark F.; Rodriguez, Carina A.; McGrath, Eric J.; Helström, Elizabeth; Liberty, Afaaf; Natukunda, Eva; Kosalaraksa, Pope; Chokephaibulkit, Kulkanya; Maxwell, Heather; Wong, Pamela; Porter, Danielle; et al. (The Lancet Child & Adolescent Health, 2021)
Bictegravir is a potent integrase strand-transfer inhibitor (INSTI) with a high genetic barrier to resistance. Bictegravir, coformulated with emtricitabine and tenofovir alafenamide, is recommended by key European and US HIV treatment guidelines as the preferred single-tablet regimen for adults and adolescents. The aim of this study was to assess the pharmacokinetics, safety, and efficacy of switching to this regimen in virologically suppressed children and adolescents with HIV. Methods In this single-arm, open-label trial, we enrolled virologically suppressed children and adolescents (aged 6 to <18 years) with HIV at 22 hospital clinics in South Africa, Thailand, Uganda, and the USA. Eligible participants had a bodyweight of at least 25 kg, were virologically suppressed (HIV-1 RNA <50 copies per mL) on a stable ART regimen for at least 6 months before screening, had a CD4 count of at least 200 cells per μL, and an estimated glomerular filtration rate of at least 90 mL/min per 1·73 m² by the Schwartz formula at screening. All participants received the fixed-dose regimen of coformulated bictegravir 50 mg, emtricitabine 200 mg, and tenofovir alafenamide 25 mg once daily. Pharmacokinetic analysis was used for dosing confirmation, and results compared with adult values. The primary outcomes were area under the curve at the end of the dosing interval (AUCtau) and concentration at the end of the dosing interval (Ctau) of bictegravir, and incidence of treatment-emergent adverse events and laboratory abnormalities at week 24. Efficacy and safety analyses included all participants who received at least one dose of study drug. We report the 48-week results. This study is registered with ClinicalTrials.gov, NCT02881320. Findings Between Sept 29, 2016 and Feb 16, 2018, we enrolled 102 participants. 100 participants received bictegravir, emtricitabine, and tenofovir alafenamide (cohort 1 [adolescents aged 12 to <18 years], n=50; cohort 2 [children aged 6 to <12 years], n=50). The mean bictegravir AUCtau was 89 100 ng × h/mL (coefficient of variation 31·0%) in adolescents (cohort 1) and 128 000 ng × h/mL (27·8%) in children (cohort 2). Compared with adults, bictegravir Ctau was 35% lower in adolescents and 11% lower in children. The 90% CIs of both parameters were within the predefined pharmacokinetic equivalence boundary and within overall range of exposures observed in adults and deemed to be safe and efficacious (geometric least-squares mean ratio [GLSM] 86·3% [90% CI 80·0–93·0] for AUCtau and 65·4% [58·3–73·3] for Ctau in adolescents; GLSM 125% [90% CI 117–134] for AUCtau and 88·9% [80·6–98·0] for Ctau for children). Bictegravir, emtricitabine, and tenofovir alafenamide was well tolerated; most adverse events were grade 2 or less in severity and no study drug-related serious adverse events were reported. One participant discontinued study drug due to adverse events (grade 2 insomnia and anxiety). Virological suppression (HIV-1 RNA <50 copies per mL) was maintained by all 100 participants at week 24 and by 98 (98%) of 100 at week 48; no participants had treatment-emergent resistance. Interpretation In adolescents and children with HIV, the bictegravir, emtricitabine, and tenofovir alafenamide singletablet regimen was well tolerated and maintained virological suppression. Our data support the treatment of HIV in adolescents and children with this single-tablet regimen. At present, the single-tablet regimen is recommended as first-line treatment in the USA for adolescents and as an alternative regimen in children and has the potential to represent an important regimen in the paediatric population.
Keywords: Bictegravir; Emtricitabine; Tenofovir alafenamide; Adolescents; Children; HIV